Distributionally Sensitive Measurement and Valuation of Population Health - Shaun Da Costa; Owen O'Donnell; Raf Van Gestel (Tinbergen Institute, 2023)
We introduce a measure of population health that is sensitive to dispersion in both age-specific health and lifespan. The measure generalises health-adjusted life expectancy without requiring more data. A transformation of change in the measure gives a distributionally sensitive monetary valuation of change in population health and disease burden. Application to Sub-Saharan Africa between 1990 and 2019 reveals that the change in population health is sensitive to allowing for lifespan dispersion but is less sensitive to age-specific health dispersion. Distributional sensitivity changes relative burdens of diseases, reduces convergence between the burdens of communicable and non-communicable diseases, and so could influence disease prioritisation. It increases the value of health improvements relative to GDP.
Keywords: I14; I15; J11; J17; O15; 330; Health; Lifespan; Life Expectancy; Inequality; Global Burden of Disease; Sub-Saharan Africa